1998
DOI: 10.1183/09031936.98.11040942
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of spirometrically controlled CT lung densitometry in a clinical setting

Abstract: aaDensitometry of the lung is extensively used in pulmonary research. It has the potential to become an important addition to standard lung function tests in diagnosing and following the extent of pulmonary emphysema and interstitial lung disease. For recent reviews of this extensive work we refer to the literature [1,2]. The value of the technique is clearly proven in pulmonary emphysema. During inspiration, computed tomography (CT) correlates well with the pathologic score of emphysema [3]. Expiratory CT ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 19 publications
1
30
0
2
Order By: Relevance
“…Notably, lung volume at end inspiration is most reproducible as compared to volumes attained in expiration, either at forced respiratory capacity (FRC) or at residual volume (RV), corresponding to end expiration and forced expiration, respectively (14,82).…”
Section: Respiratory Volumementioning
confidence: 99%
“…Notably, lung volume at end inspiration is most reproducible as compared to volumes attained in expiration, either at forced respiratory capacity (FRC) or at residual volume (RV), corresponding to end expiration and forced expiration, respectively (14,82).…”
Section: Respiratory Volumementioning
confidence: 99%
“…Consistent measurements are most likely to be achieved at maximum inspiration [353] because variation in CT lung density is lowest at full inspiration [356]; in cooperative patients, breath-holding at maximum inspiration is most reproducible [357]. A study aimed at investigating the relationship between HRCT lung attenuation measurements (employing spirometric lung volume control), pulmonary dysfunction and dyspnoea severity in patients with COPD [358], has shown that pulmonary dysfunction in COPD cannot be assessed by a single modality of lung attenuation measurements.…”
Section: Outcomes For Copd Pharmacological Trialsmentioning
confidence: 99%
“…This approach of volume correction has been shown to improve reproducibility [351,352], but its use in long-term studies may mask some of the lung density loss secondary to emphysema-related hyperinflation. The routine use of these volume-control methods in densitometric studies remains contentious [350][351][352][353][354][355].…”
Section: Outcomes For Copd Pharmacological Trialsmentioning
confidence: 99%
“…As a result, various CT image metrics have been proposed towards a more consistent and facilitated assessment. Early investigations into CT lung analysis employed relatively simple metrics, such as the mean attenuation value and other such first-order statistical measurements obtainable from the attenuation histogram [1][2][3]. More sophisticated metrics relying on texture descriptions of the parenchyma have shown promise in recent studies [4].…”
Section: Introductionmentioning
confidence: 99%